184k views
0 votes
Consider the following equilibrium: 2SO2(g) + O2(g) 2SO3(g) Which of the following is a correct equilibrium expression? Keq=[SO3][SO2][O2] Keq=[SO3]2[SO2]2[O2] Keq=[SO2][O2][SO3] Keq=[SO2]2[O2][SO3]2

User Natersoz
by
5.5k points

1 Answer

3 votes
Answer : Option B)
K_(eq) = ([SO_(3)]^(2) )/([SO_(3)]^(2) . [O_(3)]^(2))

Explanation : The equilibrium constant is often expressed in terms of the molar concentration of products divided by the product of molar concentrations of reactants.

So,
K_(eq) = ([products])/([reactants]).

Now, here in the given reaction of


2SO_(2) + O_(2) ----\ \textgreater \ 2SO_(3)

So, we have the equation for equilibrium as
K_(eq) = ([SO_(3)]^(2) )/([SO_(3)]^(2) . [O_(3)]^(2))
User Ruslan
by
5.9k points